Orem Self-Care in The Context of Nutrition Management Diabetic Foot Ulcer Patients - Eni Kusyati; Shindi Hapsari; Vina Nur Fajriyah (Sekolah Tinggi Ilmu Kesehatan (STIKes) Karya Husada Semarang, 2022)
Changes in eating patterns cause more and more people to suffer from diabetes mellitus. A proportion of the population nationally consumes sweet foods more than once a day (40.1%), sweet drinks a day (61.27%), and the behavior of consuming fatty foods and cholesterol more than once per day (41.7% ). Risky eating patterns often consume high-carbohydrate food sources, sweet drinks and foods, fatty meats, fat sources, fast food, and preserved foods9. Diabetic foot ulcer (DFU) is one of diabetes mellitus. The majority of DFUs suffer from micronutrient deficiency due to inadequate diet and lack of protein sources that should be obtained from side dishes. The study was conducted in children's care. The purpose of describing the type of food, the amount of food, food processing, and eating patterns in the context of self-care Orem. This type of research is a descriptive quantitative cross-sectional approach. In the population of people with diabetes mellitus with complications of DFU, the number of samples is 52 with a purposive sampling technique. The questionnaire uses nutrition management. The results of the study The type of food was good (71.2%), not good (28.8%), the amount of food was good (67.3%), not good (32.7%), food processing was good (75.0%), not good (25.0%), good diet (75.0%), not good (25.0%). Conclusion: Nutritional management of patients with DFU is in good and bad criteria. Keywords: diabetic foot ulcer; nutrition management; self-care orem.Self Care Orem Dalam Konteks Manajemen Nutrisi Pasien Diabetic Foot UlcerABSTRAK Perubahan pola makan menyebabkan semakin banyak menderita diabetes melitus. Proporsi penduduk secara nasional mengonsumsi makanan manis lebih dari satu kali sehari (40,1%), minuman manis lebih dari satu kali sehari (61,27%), perilaku konsusmsi makanan berlemak dan berkolesterol lebih dari satu kali per hari (41,7%). Pola makan yang berisiko sering mengkonsumsi sumber makanan tinggi karbohidrat, minuman dan makanan manis, daging berlemak, sumber lemak, makanan cepat saji serta makanan yang diawetkan. Diabetic foot ulcera (DFU) salah satu diabetes mellitus. Mayoritas DFU yang mengalami defisiensi micronutrient dikarenakan pola makanyang tidak memadai dan kekurangan sumber protein yang seharusnya didapatkan dari asupan lauk pauk. Penelitian dilakukan di anak lanang care. Tujuan mendeskripsikan jenis makanan, jumlah makanan , pengolahan makanan dan pola makan dalam konteks self care orem. Jenis penelitian Deskriptif Kuantitatif pendekatan Cross Sectional, dengan Populasi penderita diabetes militus dengan komplikasi DFU, Jumlah sampel 52 dengan Teknik Purposive Sampling. Kuesioner menggunakan manajemen nutrisi. Hasil penelitian Jenis makanan baik (71.2%),kurang baik (28.8%), jumlah makanan baik (67.3%), kurang baik (32.7%), pengolahan makanan baik (75.0%), kurang baik (25.0%), pola makan baik (75.0%), kurang baik (25.0%). Kesimpulan: Manajemen nutrisi penderita DFU dalam kriteria baik dan kurang baik . Kata Kunci : diabetic foot ulcer; manajemen nutrisi; self care orem